2012
DOI: 10.1016/j.febslet.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microRNA‐93, a new regulator of PTEN/Akt signaling pathway, in regulation of chemotherapeutic drug cisplatin chemosensitivity in ovarian cancer cells

Abstract: Edited by Tamas Dalmay Keywords:MicroRNA-93 PTEN Drug resistance Cisplatin Human ovarian cancer a b s t r a c tThe mechanisms underlying ovarian cancer cell resistance to cisplatin (CDDP) are not fully understood. MicroRNAs (miRNAs) play important roles in tumorigenesis and drug resistance. In this paper, we utilized microRNA array and real-time PCR to show that miR-93 is significantly up-regulated in cisplatin-resistant ovarian cancer cells. In vitro assays show that over-expression and knock-down of miR-93 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(133 citation statements)
references
References 40 publications
5
126
1
1
Order By: Relevance
“…Recently, several studies have shown that miRNA played an important role in chemo resistance of ovarian cancer. Mir-199b-5p is associated with acquired chemo resistance in ovarian cancer [6] and miR-93 contributes to cisplatin chemo sensitivity in ovarian cancer cells by regulating PTEN/Akt pathway [7]. Additionally, miR-29b and its signaling mechanism involved in patients with ovarian cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have shown that miRNA played an important role in chemo resistance of ovarian cancer. Mir-199b-5p is associated with acquired chemo resistance in ovarian cancer [6] and miR-93 contributes to cisplatin chemo sensitivity in ovarian cancer cells by regulating PTEN/Akt pathway [7]. Additionally, miR-29b and its signaling mechanism involved in patients with ovarian cancer [8].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (27) revealed that miR-25 promoted cell migration and invasion in ESCC. In prostate cancer and ovarian cancer, miR-93 can bind to and decrease PTEN expression, thereby promoting cancer cell proliferation and invasion (28,29). These results indicate that certain genes in the PPI network serve important roles in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…While no previous findings have characterized miR-183-5p in NPC, our data revealed a significant the correlation between miR-183-5p and the NPC N stages (p<0.05). miR-93-5p has been found to be significantly up-regulated in laryngeal squamous cell carcinoma and in cisplatinresistant ovarian cancer cells, and may promote tumor growth and angiogenesis by targeting integrin-β8 (Fu et al, 2012;Cao et al, 2013). Additionally, a decreased miR-93 expression has been implicated as a prognostic factor for colon cancer (Xiao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%